Semi-transparent organic-inorganic hybrid perovskite light-emitting diodes fabricated under high relative humidity. (March 2020) - Kim, Taejun; Kim, Jin-Hoon; Park, Jin-Woo
Highlights: Semi-transparent perovskite light-emitting diodes (st-PeLEDs) were fabricated. st-PeLEDs were prepared using solution-based fabrication under ambient air. Hydrophobic aerogel thin film passivation was coated on the perovskite film. The aerogel thin film acted as an encapsulation against very high humidity. The aerogel thin film also passivated the defects in the perovskite film. Abstract: In this study, we fabricated semi-transparent organic-inorganic hybrid perovskite light-emitting diodes (st-PeLEDs) using the solution processing of all its functional layers including the silver nanowire network (AgNW) cathode under ambient air conditions with relative humidity (RH) of over 40%. Aerogel nanoparticle film was used to passivate the film defects in the ambient air processed methylammonium lead bromide (MAPbBr3 ) perovskite nanocrystal. The semi-transparent aerogel nanoparticle film and AgNW cathode also allowed the emitted light of the st-PeLED to be transmitted through them in addition to the transmission of emitted light through the indium tin oxide (ITO) transparent anode. Under ambient air fabrication conditions with RH of over 40%, the st-PeLEDs fabricated using the optimized nitrogen (N2 ) gas blowing method provided high maximum luminance ( L ) of approximately 657 cd·m −2 emission through the bottom ITO anode and 320 cd·m −2 emission through the top AgNW cathode. Furthermore, excellent operational stability was confirmed during bending and twisting of the st-PeLEDs with aerogel passivation layer fabricated on flexible polymer substrate.